Portfolio Selection in Financial Intermediaries: A New Approach - Michaelsen, Jacob B.; Goshay, Robert C. (Journal of Financial and Quantitative Analysis, 1967)
A theoretical model capable of supporting a rigorous analysis of portfolio selection in financial intermediaries appeared only recently. In the absence of a suitable theoretical framework, the limitations of maximizing behavior as an explanation of the selection of asset and liability structures in this class of firms were obscured. Discussions bearing on this question usually focused on the structure of one or the other side of intermediary balance sheets and gave little attention to the effects of these structures on the risk associated with their equity.